The Effectiveness Smart Chart to Improve the Students Understanding in Linguistic - Rosiana, Caltira; Cahyanti, Triana Wuri (Universitas Muhammadiyah Mataram, 2022)
Difficult in understanding the saintific book, the monoutone learning method and uninteresting way to learn the Linguistic was the the classic problem which never resolved up to now. The purposes of this research are to cover the students’ problems in understanding Morphemes and Syntax Material based in virtual learning, reduce the students’ pressure and Increase the students’ motivation to learn Morphemes and Syntax material using Smart Chart. In implication, this reseach using experimental research with one group pre-test and post-test. The research was done for the English Department Students by using population and sampe is 32 students whose taken Morpheme and Syntax subject. This research designed was suitable which education atmoshere atmosphere in this era. The technique of sampling is using purposive sampling as the collecting data. Even the lecturer must be working hard and need more time to prepare the learning process, the students show the value table is 1,696 and value of t-test is 20,42. It means that Smart Chart Technique is effective and the students got good achievement.